Sexual Harassment among College Students using Public Transportation in Kathmandu Metropolitan City (One Health Journal of Nepal, 2021)
Introduction: Sexual harassment phenomena is undesirable sexual advances, needs for sexual favors, and other verbal or physical behavior of sexual nature. It is one of the most endemic types of violence toward women and girls today. The objective of this study was to find out the prevalence of harassment among female students using public transport.Methods: This was a descriptive cross sectional study, conducted among 422 female students of 3 school/colleges of Kathmandu Metropolitan City. Simple random sampling technique was used for the study area whereas for the sample population, convenience sampling was done. Data were collected by using semi structured, self-administered questionnaires based on objectives. Collected data were entered and coded in SPSS 16.0 and analyzed through descriptive statistics such as frequency, percentage data, mean and standard deviation.Results: Prevalence of sexual harassment was found to be 92% among teenage girls using public transportation in Kathmandu Valley among which physical form of harassment (59%) were mostly faced by the teenage girls. In respondents opinion, lack of laws and rules (39%) and people ignoring it (30%) were the major causes of sexual harassment in the city.Conclusions: The finding of this story shows that the rate of sexual harassment in public transportation is high. Strict Law and enforcement to the perpetrators should be done in order to reduce sexual harassment. Attitude and behavior should be changed towards women.